Cassava Flour Substitution Modulates Glycemic Responses and Glycemic Index of Wheat Breads in Apparent Healthy Volunteers. (4th July 2017) - Okafor, Ebelechukwu N.; Erukainure, Ochuko L.; Ozumba, Augusta U.; Adewale, Chris O.; Kayode, Funmi O.; Asieba, Godfrey O.; Adesegha, Olubukola I.; Elemo, Gloria N.
ABSTRACT: Different carbohydrate foods produce different glycemic responses even with little or no difference in macronutrient composition. Cassava constitutes one of the major staples in Nigeria. Four blends of cassava–wheat bread samples with 0, 10, 15, and 20% cassava flour inclusion were fed individually to groups of healthy human volunteers. Subjects were studied on separate occasions in the morning after a 10–12-hr overnight fast. Blood glucose responses were measured at intervals of 30 min over a period of 2 hr. Glucose was used as a reference food. There were normal glucose responses to the bread samples studied. Increase in cassava incorporation led to less significant glycemic responses. The glycemic index values ranged from 91–94. Results from this study indicate that the inclusion of cassava flour in bread production might not pose a threat to blood glucose response of individuals.